Smart work – production tasks management system - Chojnacki, Krzysztof; Walaszczyk, Ewa; Markowska, Aleksandra; Hernes, Marcin; Fojcik, Marcin (Smart work – system zarządzania zadaniami produkcyjnymi, 2021)
The intensive development of Enterprise Resource Planning (ERP) is caused by huge competition on the production market and thus the need to optimize costs, efficiency and production time. However, the integration problem is still unresolved. One of the main problems is related to monitoring the realisation of production. In many ERP systems, this issue is very weakly performed. Data from different sub-systems are not fully integrated, therefore the process of decision-making is very difficult. The main purpose of the research described in this paper was to develop a prototype of a module for the settlement of production tasks in an integrated ERP-class system. The problems related to the module of the settlement of tasks of production workers, and online presentation of employee performance and machine condition was analysed.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 4 (62), s. 1-9
Keywords: Enterprise Resource Planning; ERP; production tasks management; system integration; systemy klasy ERP; zarządzanie zadaniami produkcyjnymi; integracja systemów